2012
DOI: 10.1007/s10900-012-9609-1
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Obesity and Its Impact on Reproductive Health Outcomes Among Urban Women

Abstract: This prospective survey study assessed the knowledge of reproductive outcomes that are affected by obesity among women in an urban community. A total of 207 women attending a community fair on the south side of Chicago participated in the study. A survey assessing knowledge of BMI and of the effects of obesity on general, cardiometabolic and reproductive health outcomes was administered. Subjects ranged in age from 18 to 70 years (mean ± SD, 48.6 ± 12.9 years) and ranged in BMI from 17.3 to 52.1 kg/m2 (mean ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 28 publications
4
30
6
Order By: Relevance
“…25 As women of reproductive age will be responsive to education on consequences of obesity on reproductive health, elaborate information needs to be widely disseminated in the community to bring about behavioral modifications. 15 Awareness of increased risk of caesarean deliveries was stated by 30.8% 15 26 of participants in other studies were more than our observations. The awareness of congenital anomalies among offspring was 23.7% in a study done in Chicago 15 and 58% in a study done in Brisbane 23 in comparison to 26.4% reported by participants in this study.…”
Section: Discussioncontrasting
confidence: 45%
See 4 more Smart Citations
“…25 As women of reproductive age will be responsive to education on consequences of obesity on reproductive health, elaborate information needs to be widely disseminated in the community to bring about behavioral modifications. 15 Awareness of increased risk of caesarean deliveries was stated by 30.8% 15 26 of participants in other studies were more than our observations. The awareness of congenital anomalies among offspring was 23.7% in a study done in Chicago 15 and 58% in a study done in Brisbane 23 in comparison to 26.4% reported by participants in this study.…”
Section: Discussioncontrasting
confidence: 45%
“…15 Awareness of increased risk of caesarean deliveries was stated by 30.8% 15 26 of participants in other studies were more than our observations. The awareness of congenital anomalies among offspring was 23.7% in a study done in Chicago 15 and 58% in a study done in Brisbane 23 in comparison to 26.4% reported by participants in this study. Another Australian study observed that awareness of the role of obesity in maternal complications was much more for maternal than neonatal complications which was similar to our findings.…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations